Pengaruh Perawatan Metode Kanguru (PMK) terhadap Pencegahan Hipotermi pada Bayi Baru Lahir: Effects of Kangaroo Mother Care (KMC) on Prevention of Hypothermia in Newborns - Parti; Malik, Sumiati; Nurhayati (Jurnal Bidan Cerdas, 2020)
Most causes of infant death are problems that occur in newborn/neonatal (0-28 days old), Low Birth Weight Babies (LBW) is one of the factors which has a contribution to infant mortality, especially in the neonatal period. Infant Mortality Rate (IMR) is a benchmark in determining the degree of public health, both at the National and Provincial levels. This study aimed to determine the effect of the Kangaroo Mother Care Method (KMC) on the prevention of hypothermia in low birth weight infants at Morowali District Hospital in 2019. The type of research used was a quasi-experiment. The population is all low birth weight babies born from May to July 2019. The sample in this study was all newborns with low birth weight born from May to July 2019, totaling 30 babies. There is a difference (influence) on the baby's body temperature before and after KMC with a p-value=0,000. The kangaroo mother care can continue to be affiliated considering its benefits for both infants and mothers, as well as increasing the ability of health workers in conducting KMC so that they can provide in-house training for mothers to be carried out at home.